Intersection of Epigenetic and Immune Alterations: Implications for Fetal Alcohol Spectrum Disorder and Mental Health - Lussier, Alexandre A.; Bodnar, Tamara S.; Weinberg, Joanne (Frontiers in Neuroscience, 2021)
Prenatal alcohol exposure can impact virtually all body systems, resulting in a host of structural, neurocognitive, and behavioral abnormalities. Among the adverse impacts associated with prenatal alcohol exposure are alterations in immune function, including an increased incidence of infections and alterations in immune/neuroimmune parameters that last throughout the life-course. Epigenetic patterns are also highly sensitive to prenatal alcohol exposure, with widespread alcohol-related alterations to epigenetic profiles, including changes in DNA methylation, histone modifications, and miRNA expression. Importantly, epigenetic programs are crucial for immune system development, impacting key processes such as immune cell fate, differentiation, and activation. In addition to their role in development, epigenetic mechanisms are emerging as attractive candidates for the biological embedding of environmental factors on immune function and as mediators between early-life exposures and long-term health. Here, following an overview of the impact of prenatal alcohol exposure on immune function and epigenetic patterns, we discuss the potential role for epigenetic mechanisms in reprogramming of immune function and the consequences for health and development. We highlight a range of both clinical and animal studies to provide insights into the array of immune genes impacted by alcohol-related epigenetic reprogramming. Finally, we discuss potential consequences of alcohol-related reprogramming of immune/neuroimmune functions and their effects on the increased susceptibility to mental health disorders. Overall, the collective findings from animal models and clinical studies highlight a compelling relationship between the immune system and epigenetic pathways. These findings have important implications for our understanding of the biological mechanisms underlying the long-term and multisystem effects of prenatal alcohol exposure, laying the groundwork for possible novel interventions and therapeutic strategies to treat individuals prenatally exposed to alcohol.